Forward-Reverse Osmosis Processes for Oily Wastewater Treatment - Hasan Farhood Makki; Noor Hammood Zghair (Journal of Engineering, 2023)
In this study, the feasibility of Forward–Reverse osmosis processes was investigated for treating the oily wastewater. The first stage was applied forward osmosis process to recover pure water from oily wastewater. Sodium chloride (NaCl) and magnesium chloride (MgCl2) salts were used as draw solutions and the membrane that was used in forward osmosis (FO) process was cellulose triacetate (CTA) membrane. The operating parameters studied were: draw solution concentrations (0.25 – 0.75 M), oil concentration in feed solution (FS) (100-1000 ppm), the temperature of FS and draw solution (DS) (30 - 45 °C), pH of FS (4-10) and the flow rate of both DS and FS (20 - 60 l/h). It was found that the water flux and oil concentration in FS increase by increasing the concentration of draw solutions, the flow rate of FS and the temperature for a limit (40oC), then, the water flux and oil concentration decrease with increasing the temperature because of happening the internal concentration polarization phenomenon. By increasing the oil concentration in FS and the flow rate of the DS, the water flux and oil concentration in FS decreased, while it had a fluctuated behavior with increasing pH of oily wastewater. It was found also that MgCl2 gives water flux higher than NaCl. So the values of resistance to solute diffusion within the membrane porous support layer were 55.93 h/m and 26.21 h/m for NaCl and MgCl2 respectively. The second stage was applied reverse osmosis process using polyamide (thin film composite (TFC)) membrane for separating the fresh water from a diluted (NaCl) solution using different parameters such as draw solution concentration (0.08–0.16 M), feed flow rate (20–40 l/h).